Mining frequently changing interesting XML data from historical XML documents - Qiu, Colin Weixing. (2010)
In the recent years, a large amount of work has been done and researched on XML data mining. Most of these existing works assumed that the XML data is static and focuses on the snapshot XML data, when XML data is dynamic in real applications. Mining of XML data is useful in many different applications like XML change detection. This project’s objective would revolve around detecting changes in XML data over many historical versions of XML documents and would involve a novel approach to extract out the substructure or nodes which are frequently and significantly evolving.